Islamism, radical islam, jihadism : the problem of language and islamophobia - Paul, Hedges (2015)
There are problems with terms used to discuss religiously justified violence, like Islamism, Radical Islam, Jihadism, etc. They may provide legitimacy to terrorists, increase Islamophobia, and distort or misrepresent the actions and ideologies they seek to describe.